2023
DOI: 10.30564/agger.v5i4.5949
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality Assessment in Pul-e-Charkhi Region, Kabul, Afghanistan

Hafizullah Rasouli,
Ashok Vaseashta

Abstract: We present the results of studies conducted on the assessment of groundwater quality observed on several water samples taken from water supply sources in the Pul-e-Charkhi region, which is located near the eastern part of Kabul and has seen steady growth in population after the U.S. completed its withdrawal from Afghanistan on 30 August 2021. The water in the basin serves as the main source of water supply and it consists of water discharge from nearby local industries, automobile repair and wash, Osman House,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Rasouli and Vaseashta [1] studied groundwater quality assessment in Pul-e-Charkhi region, Kabul, Afghanistan for different types of usage, such as drinking water, agriculture, and industries. The study presented the assessment of groundwater quality observed on several water samples taken from water supply sources in the Pul-e-Charkhi region, which is located near the eastern part of Kabul and has seen steady growth in population after the U.S. military left Afghanistan.…”
Section: Summary Of Paper Presented In Vol 5 Issue 4 (2023)mentioning
confidence: 99%
“…Rasouli and Vaseashta [1] studied groundwater quality assessment in Pul-e-Charkhi region, Kabul, Afghanistan for different types of usage, such as drinking water, agriculture, and industries. The study presented the assessment of groundwater quality observed on several water samples taken from water supply sources in the Pul-e-Charkhi region, which is located near the eastern part of Kabul and has seen steady growth in population after the U.S. military left Afghanistan.…”
Section: Summary Of Paper Presented In Vol 5 Issue 4 (2023)mentioning
confidence: 99%